The atractiveness of polish geological museums - Parzych, Krzysztof; Walczak, Paulina; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
The Geological and natural museums to the oldest museum objects in Poland. Their rise is associated more often with another person who is not able to meet the expectations of others. The attractiveness of geological museums from a variety of collections, accompanied by exhibitions, films, slides with the use of multimedia techniques, has become extremely attractive to visitors. In Poland there are currently 56 other objects, including arrangements of exhibits of geological specimens. The most visited are the objects with an open exhibition: the Museum of Krakow's Saltworks in Wieliczka, the Tatra Museum and the Museum of Natural History in Międzyzdroje.